2011
DOI: 10.1039/c1cc10554j
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of multiple pathways capable of emitting peroxyoxalate chemiluminescence using a charge coupled devicespectrometer

Abstract: Peroxyoxalate chemiluminescence (PO-CL) spectra obtained simultaneously and continuously using a CCD spectrometer provide evidence of the complexity of PO-CL reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Fig. The possible CRET mechanism in guanine chemiluminescence reaction may be similar to chemically initiated electron exchange luminescence (CIEEL) mechanism of peroxyoxalate chemiluminescence (Lee et al, 2002a(Lee et al, , 2002bMaruyama et al, 2013;Park et al, 2011). The ratio determined with 100 s measurement was the smallest.…”
Section: Interaction Between Tba and Go In Guanine Chemiluminescencementioning
confidence: 83%
“…Fig. The possible CRET mechanism in guanine chemiluminescence reaction may be similar to chemically initiated electron exchange luminescence (CIEEL) mechanism of peroxyoxalate chemiluminescence (Lee et al, 2002a(Lee et al, , 2002bMaruyama et al, 2013;Park et al, 2011). The ratio determined with 100 s measurement was the smallest.…”
Section: Interaction Between Tba and Go In Guanine Chemiluminescencementioning
confidence: 83%
“…Among the several peroxides proposed so far as the high-energy intermediates (HEIs) capable of generating the excited fluorophores during their decomposition, the four-membered cyclic peroxides, such as 4-aryloxy-4-hydroxy-1,2-dioxetane-3-one (DOT) and 1,2-dioxetne-3,4-dione (DOD), have been the most frequently proposed [3,4,6,7,9,10,14,19,21,22]. However, these intermediates have never been captured nor isolated.…”
Section: Introductionmentioning
confidence: 99%
“…Interaction between fluorescent dye and high-energy intermediate formed from the reaction of guanine and TMPG is similar to that between fluorescent dye and high-energy intermediate from peroxyoxalate chemiluminescence reaction (Augusto et al, 2013;Lee et al, 2003;Maruyama et al, 2013;Park et al, 2011) even though the former is generated by the intra-CRET (Cho et al, 2014), whereas the latter is observed by the inter-CRET.…”
Section: Sequence Effect Of Ssdnas In Guanine Chemiluminescencementioning
confidence: 76%